Revealing the early ice flow patterns with historical Declassified Intelligence Satellite Photographs back to 1960s - Shujie Wang; Hongxing Liu; Bailang Yu; Guoqing Zhou; Xiao Cheng (Geophysical Research Letters)
Abstract The reconnaissance ARGON satellites collected the earliest images of Antarctica from space dating back to the 1960s, providing valuable historical baseline information for studying polar ice sheets. Those photographs are underutilized for ice motion mapping, due to lack of sufficient ground controls for image orthorectification. In this study, we orthorectified the ARGON photographs by fully exploiting the metric qualities of WorldView satellite images: very high spatial resolution and precise geolocation. Through a case study over Larsen Ice Shelf, we demonstrated that the camera model with bundle block adjustment can achieve geolocation accuracy of better than the nominal resolution (140 m) for orthorectifying ARGON images, with WorldView imagery as ground control source. This allowed us to extend the ice velocity records of Larsen Ice Shelf back into 1960s~1970s for the first time. The retrospective analysis revealed that acceleration of the collapsed Larsen B occurred much earlier than previously thought.